A matrix inequality based design method for consensus problems in multi-agent systems - Zhai, Guisheng; Okuno, Shohei; Imae, Joe; Kobayashi, Tomoaki (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we study a consensus problem in multi-agent systems, where the entire system is decentralized in the sense that each agent can only obtain information (states or outputs) from its neighbor agents. The existing design methods found in the literature are mostly based on a graph Laplacian of the graph which describes the interconnection structure among the agents, and such methods cannot deal with complicated control specification.
Keywords: multi-agent systems; consensus; decentralized control; graph Laplacian; matrix inequality; LMI